Pengaruh Anggaran Produksi dan Anggaran Operasional Terhadap Pertumbuhan Bisnis Gilingan Bakso Margi Utomo, Bekasi Utara - Synta Maharrany; Susi Aulia; Arlan Dhani Armansyah; Arjuna Bintang Pratama; Desya Amanda; Husni Mubarok (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study aims to analyze the extent to which the production budget and operational budget influence business growth at Gilingan Bakso Margi Utomo in North Bekasi. The research is motivated by the increasing importance of effective financial management and budgeting in navigating the challenges of a highly competitive and dynamic business environment. A quantitative approach was used in this study, with data collected through observation, intervies, and the distribution of questionnaires to 28 respondents directly involved in the business management. The variables analyzed include Production Budget (X1), Operational Budget (X2), and Business Growth (Y). Data analysis was conducted using multiple linear regression, preceded by tests for validity, reliability, and classical assumption testing (normality, multicollinearity, and heteroscedasticity). The results reveal that both production and operational budgets significantly affect business growth, both individually and collectively. These findings highlight the critical role of sound budget management as a fundamental driver of stable and sustainable business development. Moreover, the study provides strategic insights for small business owners seeking to enhance their competitiveness and financial efficiency.